Приближение классов Cψ¯Hω суммами Валле Пуссена - Рукасов, В.И.; Чайченко, С.О. (Український математичний журнал, 2002)
Розгляпуто деякі питання наближення классів Cψ¯Hω, внедеиих О. I. Степанцем у 1996 р., сумами Валле Пуссена. Знайдено асимптотичні рівності, які в деяких випадках забезпечують розв'язок задач1 Колмогорова-Нікольського для сум Валле Пуссена на класах Cψ¯Hω. We investigate the problem of the approximation of the classes Cψ¯Hω introduced by Stepanets in 1996 by the de la Valée-Poussin sums. We obtain asymptotic equalities that give a solution of the Kolmogorov–Nikol'skii problem for the de la Valée-Poussin sums on the classes Cψ¯Hω in several important cases.